Youth Organization Participation in Development in Marawas Village, Minahasa Regency - Kiroyan Anugrah; Sendouw Recky; Mantiri Jeane; Rantung Margareth (SHS Web of Conferences, 2022)
This study aims to determine community participation, especially youth who join youth organizations in development in the marawas village, north tondano district. This study uses a qualitative approach with data collection techniques of observation, documentation, and interviews. The data analysis results show that 1) youth organizations do not always play an active role in decision-making. 2) youth organizations are only involved in small-scale government activities. 3) the community does not directly feel the benefits of the youth organization. 4) youth organizations need a large budget to implement each program effectively. Based on the data analysis, it is recommended. 1) it is better for youth organizations to have a more active role in decision-making. 2) youth organizations should carry out small and large-scale activities. 3) the community should feel directly the benefits of the youth organization. 4) evaluation of youth group participation should require a budget.